The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3758/s13420-020-00425-6
|View full text |Cite
|
Sign up to set email alerts
|

Asking for help: Do dogs take into account prior experiences with people?

Abstract: When confronted with a difficult or impossible problem, dogs tend to look back at humans and try to catch their attention, instead of trying to solve it themselves. This behavior has been interpreted as a help request, but it is debated whether dogs take into account prior experiences with people when selecting whom to turn to. In the present study, dogs were trained to discriminate between a generous experimenter who gave them food and a selfish one that took it away. After assessing that they had established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…The gender of the experimenter could also be a contributing factor, since male and female dogs may show a different behavioral response to men compared to women [ 37 , 43 , 84 ]. However, as the tests were always performed by a woman and 95.3% of the owners in our data were female, it was not possible to investigate the effect of human gender on test performance of the dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender of the experimenter could also be a contributing factor, since male and female dogs may show a different behavioral response to men compared to women [ 37 , 43 , 84 ]. However, as the tests were always performed by a woman and 95.3% of the owners in our data were female, it was not possible to investigate the effect of human gender on test performance of the dogs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, wolves and other species tend to attempt to solve the problem independently, even when raised with humans from birth [ 35 , 36 ]. The dogs’ human-directed gazing behavior has been interpreted as a social problem-solving strategy, and as a request for help from the human [ 27 , 34 , 37 , 38 ]. This behavior shows individual and breed variation [ 39 ] and seems to also have a genetic component [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dogs were included if either purebred or crosses between two breeds from within the same target breed group; crossbreeds between different breed groups were excluded. Both experimenters and all included owners were female, since a study indicated that dogs prefer to gaze at women compared to men (Carballo et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, several studies support the notion that dogs’ human-directed gazing in unsolvable tasks is a social-communicative behaviour (Carballo et al 2020 ; Cavalli et al 2020 ; Mendes et al 2021 ). An indication of help-seeking, as opposed to random gazing at salient objects, could be if dogs direct their gaze differentially at the present persons, depending on their current role in the task or past experiences and reinforcement history.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates that dogs distinguished between the cooperative and competitive partner based on their direct experience. Moreover, two studies by Carballo et al [ 17 , 18 ] showed that dogs preferred to approach and gazed more at a generous human than a selfish one in a food-giving situation [ 17 ] and when confronted with an unsolvable task [ 18 ]. However, other studies have found that dogs could not form reputations of humans after direct experience–Piotti et al [ 19 ] could not demonstrate that dogs formed a reputation of an experimenter based on her skilfulness or the quality of the interaction and McGetrick et al [ 20 ] found that dogs did not prefer a helpful human, who provided them with food by activating a food dispenser, compared to an unhelpful human, who did not provide them with food, which suggests that they did not form reputations of the humans based on their cooperativeness.…”
Section: Introductionmentioning
confidence: 99%